Jaundice during pregnancy: maternal and fetal outcome - Krishnamoorthy, Jayanthi; Murugesan, Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Jaundice affects a small percentage of pregnant women, yet it takes a major toll on health of both mother and fetus especially in developing countries like India. Jaundice in pregnancy carries a grave prognosis for both the fetus and the mother, and is responsible for 10% of maternal deaths. The aim of the study was to find out the effect of jaundice during pregnancy on maternal and fetal outcome. Methods: 51 pregnant women with jaundice during pregnancy attending the Institute of obstetrics and gynaecology, Egmore, Chennai between 2011-2012. Results: 51 patients had jaundice during pregnancy. The incidence of jaundice was 0.29%.74% of patients was between 20-29 years of age. Maximum numbers of cases were Primigravida. The most common cause of jaundice was Viral Hepatitis. Maternal mortality was 7.8%.The common maternal complications were atonic postpartum haemorrhage 9.8%, hepatic encephalopathy 7.87%, disseminated intravascular coagulation 5.88% and hepatorenal failure 4%. Perinatal mortality was 35.5%. Conclusions: Jaundice in pregnancy has adverse fetomaternal outcome. Improvement in health awareness, education and regular antenatal checkups, early referrals result in early diagnosis and treatment of jaundice during pregnancy thus reducing maternal and fetal mortality and morbidity.